Discriminación de género en la contratación pública en los últimos diez (10) años del siglo XXI en Colombia (2021)
This document will produce a compilation of literature on gender discrimination in government procurement over the past ten (10) years in Colombia, recognizing how it can have a high impact on the country's economy. Through an analysis of documents on the gender gap, government procurement, among others. Which helped identify how such discrimination reflects the decrease in opportunities for women in the workplace.women in the workplace.